Estimating age in elderly individuals: a morphological and quantitative approach using the pubic symphysis - Mansour, Cindy; Márquez-Grant, Nicholas; Cunha, Eugénia; Lescure, Javier; García Velasco, María; Benito Sánchez, María (Springer, 2026)
Estimating age in elderly adults is particularly challenging in forensic anthropology due to accelerated skeletal degeneration that varies greatly among individuals and the reduced precision of existing methods for advanced age groups. This study examines eight pubic symphyseal features in 228 documented individuals aged 60 or older from contemporary skeletal collections in Portugal and Spain, and incorporates pubic bone weight to evaluate its relationship with increasing age. Regression tree analysis identified two late-adult phases (Phases 1 and 2), which align with refined versions of the Suchey–Brooks, Hartnett, and Berg Phases VI and VII. The method demonstrated strong intra- and interobserver reliability (ρ = 0.77–0.97 and ρ = 0.58–0.75), minimal bias (− 4.75 to + 3.12), and acceptable inaccuracy (1.78–8.12 years). Pelvic bone weight showed a moderate negative correlation with age (ρ = −0.44, p < 0.01), and no significant bilateral differences or effects from hip prostheses were observed. This refined method provides a reproducible approach for estimating age in elderly individuals, improving overall accuracy and applicability. Further validation with additional samples from other populations is recommended.
Keywords: 32 Biomedical and Clinical Sciences; Aging; Clinical Research; Legal & Forensic Medicine; 3199 Other biological sciences; 3202 Clinical sciences; 3499 Other chemical sciences; Forensic science; Forensic anthropology; Age estimation; Adult individuals; Spanish sample; Portuguese sample; Pubic symphysis